CONSUMPTION, ELASTICITY AND DEMAND ESTIMATION OF ANIMAL SOURCES FOOD IN INDONESIA - Esty Asriyana Suryana; Drajat Martianto; Yayuk Farida Baliwati (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2021)
Intake of animal protein in food consumption patterns is very decisive for a person to live a healthy, active, and productive life. This study aims to analyze of consumption and estimation of food demand for animal sources in Indonesia. This analysis used the AIDS model to estimate the elasticity of food demand and use linear equations to estimate food demand of animal sources in 2020-2025. Results showed the consumption of food for animal sources in Indonesia still did not meet the recommended nutritional adequacy rates. Animal commodities are responsive to prices and income changes. The value of the elasticity of demand for animal food was all negative accordance with the law of demand which has a negative direction. For income elasticity the value of income elasticity for whole animal protein source food commodities was positive. The estimation of consumption showed that the demand for animal meat in the period 2020-2025 continues to increase along with income and population growth. To meet the need of animal protein, in addition to the current program to achieve food of animal sources self-sufficiency, it is necessary to strive to increase production based on minimum food demand estimation.